Impact of tidal mixing on mixed layer depth variability in the Northern Bay of Bengal - Nur Hidayat Muh.; Wafdan Reza; Ramli Marwan; Muchlisin Zainal A.; Muhammad Muhammad; Rizal Syamsul (BIO Web of Conferences)
This study aimed to investigate the influence of tidal mixing on the Mixed Layer Depth (MLD) in the Northern Bay of Bengal (NBoB), providing insights into regional variations in oceanic mixing processes. The data used in this study consisted of daily MLD observations over a two-year period (2022–2023) from the Copernicus Marine Environment Monitoring Service (CMEMS) data portal. The analysis focused on three regions within the NBoB, determined based on the Simpson-Hunter (SH) parameter calculations which indicate the intensity of tidal mixing. The first region, identified by low tidal mixing (evidenced by a high SH parameter), is located between 85°E-87°E and 18.5°N-20°N. The second region, characterized by high tidal mixing (or low SH parameter), spans 90°E-92°E and 21°N-23°N. The third region, with moderate tidal mixing, covers 92°E-94°E and 18.5°N- 20.5°N. The study reveals that Region 1 has the highest average MLD (14.85 m), Region 2 has the lowest average MLD (9.02 m), and Region 3 has an intermediate MLD (12.58 m). These findings highlight an inverse relationship between tidal mixing intensity and MLD, with stronger tidal mixing linked to shallower MLD.